Prison life and prior social experiences: understanding their importance for indigenous peoples’ re-entry outcomes - Ryan, Nicole (The British journal of criminology, 2019)
This study explores whether differences in Indigenous and non-Indigenous peoples’ risk of reincarceration can partially be explained by their social experiences prior-to-prison and their prison-life experiences. Using administrative and self-report data from 1,238 incarcerated Indigenous (n =303) and non-Indigenous (n = 935) people in Australia, we conducted a series of Cox proportional hazards regressions. We found that Indigenous people had a significantly increased risk of reincarceration compared to non-Indigenous people, and that this can partially be explained by social experiences prior-to-prison. However, after conducting multivariate analyses, the association between prison life-experiences and reincarceration was attenuated to the null. The implications for policy and theory are discussed.